Traditional vs. digital: A framework for tourism destination marketing planning process - Sonja Zlatanov; Marko Gašić; Jelena Janković-Filipović (BizInfo)
Tourism destinations represent a central element of research in tourism, given that the majority of the tourist activities take place in them. Accordingly, this paper is aimed at highlighting the importance of adequate strategic management of tourism destinations, as well as the key role of strategic marketing management of tourism destinations. This paper presents the review of literature devoted to the stages of the tourism destination marketing planning process, as well as the literature devoted to the differences between traditional and digital marketing planning process in all sectors, without directly focusing on tourism. Accordingly, the contribution of this paper lies in connecting the two subjects and proposing the framework for tourism destinations digital marketing planning process.